2019
DOI: 10.1002/ppp3.10091
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between birds and flowers of Rhododendron spp., and their implications for mountain communities in Nepal

Abstract: Societal Impact StatementPlant–pollinator relationships are fundamentally important for the conservation of the terrestrial biodiversity that rural communities in low‐income countries rely upon. In Nepal, a country that is biologically rich but economically poor, Rhododendron forests provide a range of ecosystem services that are under threat from overexploitation and climate change. Here, we suggest a vital role for pollinating birds in ensuring the sexual reproduction, and thus the long‐term survival, of Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Te study showed highest Importance Value Index (IVI) of Tsuga dumosa, Rhododendron species, and Shima wallichi was the highest in Kalobhir, Bolde Setidevi, and Simpani CF respectively because these are the most preferred species of users group. Te Rhododendron spp, Abies spectabilis and Juniper spp are dominating tree species in high altitude area [45,46] but Schima wallichi is dominant species in midhills [47,48]. Te IVI is determined the by species dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Te study showed highest Importance Value Index (IVI) of Tsuga dumosa, Rhododendron species, and Shima wallichi was the highest in Kalobhir, Bolde Setidevi, and Simpani CF respectively because these are the most preferred species of users group. Te Rhododendron spp, Abies spectabilis and Juniper spp are dominating tree species in high altitude area [45,46] but Schima wallichi is dominant species in midhills [47,48]. Te IVI is determined the by species dominance.…”
Section: Discussionmentioning
confidence: 99%
“…The red morphs with large showy flowers produce large amounts of relatively diluted nectar, which is rich in phenolics; these traits follow ornithophily ( Faegri and van der Pijl, 1979 ). In Langtang National Park, Central Himalaya, Nepal, several species of birds have been recorded to visit R. arboreum mainly for nectar consumption ( Ollerton et al., 2020 ). In our work, the Chestnut-crowned laughing thrush, Streaked laughingthrush, and Himalayan bulbul were the most frequent pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in R. arboreum , there is a noticeable difference in floral color at different elevations. At lower altitudes, the trees exclusively bear red flowers, and those at higher altitudes, the trees bear pink flowers ( Ollerton et al., 2020 ). However, whether these color morphs differ in other reproductive traits as well, has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the radiations of Erica in South Africa (Pirie et al, 2011), Styphelioideae in Australia (Johnson, 2013), and Rhododendron in the Himalayas. In the case of Rhododendron , many species are red‐flowered and pollinated by passerine birds (Huang et al, 2017; Ollerton et al, 2020). Curiously, members of the East Asian genus Agapetes G.Don (Vaccinioideae) also possess pendant, red flowers that are presumably not easily accessed by passerine birds and therefore seem to require a hovering vector for effective pollination (Figure 1M).…”
Section: Figurementioning
confidence: 99%